Pemberdayaan Masyarakat Tani melalui Penerapan Sistem Pertanian Terpadu di Nagari Singkarak, Kecamatan X Koto Singkarak, Kabupaten Solok - Delvi Yanti; Mislaini Rahman (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
The objectives of KKN-PPM activity are: 1) The method of utilizing the wastes of agriculture and stock husbandry as the media source of production oriented at the quality of outcome and the preservation of environment; and 2) The formation of sustainable integrated farming centers. The methods of activity applied are participation and action that involve the groups of target society and students who act as the facilitators. This activity was followed by 28 students partnering with Cimpago Putih farmer group. The results achieved on this activity are that the target groups have understood the method of utilizing the wastes of agriculture and stock husbandry, and together with the students made the demonstration plot of integrated farming system. The results achieved on each demonstration plot are: 1) The demonstration plot of mina paddy namely the growths of paddy and fish that look good; 2) The demonstration plot of combining fishery and stock husbandry, namely to decrease the contamination of environment by chicken manure; 3) The demonstration plot of biogas made of cow dung, namely gas (formed after 20 days from the first refill) and liquid compost (the sludge of biogas by-product) with the particle composition of nitrogen (2.59%), phosphor (0.022%), and kalium (4.01%); 4) The demonstration plot of compost from the waste of agriculture namely solid compost (straw and kirinyuh) with the particle composition of nitrogen, phosphor, and kalium are 2.14, 0.407, and 1.79%; and 5) the demonstration plot of cultivation and processing of forage namely the better growth of elephant grass with the ratio of alive and dead elephant of 30:1 and the paddy straw of ammoniation (the smell of ammonia, the color of brown green, and none fungus).